An Analysis of Relationship between Los Angeles Abrasion Value and Aggregate Crushing Value - Malepati, Ram Kumar; Gautam, Gopal (Journal of Advanced College of Engineering and Management, 2026)
The physical properties of materials used in the base course of pavement play a critical role in determining the quality of road construction. Aggregates from different river sources exhibit varying physical, chemical, and geotechnical properties. The objective of the study is An Analysis of Relationship between Los Angeles Abrasion Value and Aggregate Crushing Value. Focusing on strength and durability based on laboratory test results to evaluate their suitability according to the "Standard Specification for Road and Bridge Works 2016 (2nd Amendments 2022)". Base course aggregate samples from within Major River sources in Madesh Province of Nepal was collected for this research. According to the IS code and the manual of standard tests by the department of roads, laboratory tests was conducted on 66 samples of 22 location of 22 river to determine Los Angeles abrasion value and aggregate crushing value. Out of these, 21 samples met the specified requirements. Fifteen suitable samples was selected for regression analysis to evaluate the relationship and establish the relationship between the Los Angeles abrasion value and aggregate crushing value. The remaining six suitable samples was used for model validation. The results show strong relationship between Los Angeles abrasion value and Aggregate Crushing Value as: LAAV= 1.2811× ACV + 8.0895 The R - square values was found to be 0.841 respectively. From model validation, the R - square values was found 0.7646 the predicted value of Los Angeles abrasion value against actual values of Los Angeles abrasion value, respectively. Therefore, the Aggregate Crushing Value test is used as a substitute test for the Los Angeles abrasion value tests.